Influence of weather situation on non-CO 2 aviation climate effects: the REACT4C climate change functions - Frömming, Christine; Grewe, Volker; Brinkop, Sabine; Jöckel, Patrick; Haslerud, Amund S.; Rosanka, Simon; van Manen, Jesper; Matthes, Sigrun (Atmospheric Chemistry and Physics, 2021)
Emissions of aviation include CO2, H2O, NOx, sulfur oxides, and soot. Many studies have investigated the annual mean climate impact of aviation emissions. While CO2 has a long atmospheric residence time and is almost uniformly distributed in the atmosphere, non-CO2 gases and particles and their products have short atmospheric residence times and are heterogeneously distributed. The climate impact of non-CO2 aviation emissions is known to vary with different meteorological background situations. The aim of this study is to systematically investigate the influence of characteristic weather situations on aviation climate effects over the North Atlantic region, to identify the most sensitive areas, and to potentially detect systematic weather-related similarities. If aircraft were re-routed to avoid climate-sensitive regions, the overall aviation climate impact might be reduced. Hence, the sensitivity of the atmosphere to local emissions provides a basis for the assessment of weather-related, climate-optimized flight trajectory planning. To determine the climate change contribution of an individual emission as a function of location, time, and weather situation, the radiative impact of local emissions of NOx and H2O to changes in O3, CH4, H2O and contrail cirrus was computed by means of the ECHAM5/MESSy Atmospheric Chemistry model. From this, 4-dimensional climate change functions (CCFs) were derived. Typical weather situations in the North Atlantic region were considered for winter and summer. Weather-related differences in O3, CH4, H2O, and contrail cirrus CCFs were investigated. The following characteristics were identified: enhanced climate impact of contrail cirrus was detected for emissions in areas with large-scale lifting, whereas low climate impact of contrail cirrus was found in the area of the jet stream. Northwards of 60∘ N, contrails usually cause climate warming in winter, independent of the weather situation. NOx emissions cause a high positive climate impact if released in the area of the jet stream ...